Developing a new questionnaire of positive contributions to Chinese families by children with autism spectrum disorder - Shulan Zeng; Afsheen Sardar; Amoneeta Beckstein; Noor Hassline Mohamed; Renhong Shen; Yunhui Xiu (SAGE Publications, 2024)
Background and Aims A literature review of both Eastern and Western literature regarding families of children with autism spectrum disorder (ASD) revealed limited empirical research that examines ASD in China. Furthermore, most research in this area comes from a deficit model and there is a lack of research that comes from a strengths background. No previous study in China has looked at the positive contributions of children with ASD to their families. The present study came from a strengths-based perspective and aimed to develop a new questionnaire to evaluate the positive contributions made to families by children who have ASD in China and are raised by their respective families. It considered the severity level of the children's disorder and the impact this had on the parents. Besides examining the children's impairment levels, the study also examined positive contributions and their relationship with socio-demographic elements such as family income and employment status of the parents, which also seem to be related to the positive contributions experienced by the parents. Methods First, based on the literature review, an initial qualitative interview protocol was developed and administered to 10 parents of children with ASD. Then, based on the analyses of the interviews, a quantitative questionnaire was developed to assess the positive contributions of children with ASD to their families. The questionnaire was then administered to 156 parents of children with ASD. The internal structure of the questionnaire was analyzed by factor analysis. The questionnaire's reliability and validity were also examined. The data were then analyzed with multiple correlation comparisons and an independent sample T-test. Results Six factors emerged for families of children with ASD. The results showed that the cumulative explanatory variance of the six dimensions of the questionnaire was 65.42%. The Cronbach’s coefficient of each dimension was between 0.7 and 0.9, and the combined Cronbach’s coefficient of the total questionnaire was 0.945. This study found that the overall average positive contribution to families by children with ASD was 3.32, which is at a medium level, and all six dimensions were at a medium-to-high level. This study also found that the family's monthly income contributed to the overall positive contribution, intimacy and happiness, and gaining more special knowledge through experience dimensions. Furthermore, it was found that moderate severity of ASD, high income, and parental employment were all associated with more positive contributions. Conclusion This new questionnaire appears to have good reliability and validity and seems suitable for assessing the positive contributions to families by children with ASD in China. Implications The present study may be helpful for the parents of children with ASD and will likely help them focus on the strengths of their children rather than their shortcomings. The study might also benefit counselors and researchers who would be able to use the new questionnaire to evaluate the positive contributions made to families by children who have ASD.